Deciphering the biological processes in root hairs required for N-self-fertilizing cereals - Pree, Simon; Malekian, Babak; Sandén, Hans; Nicolaisen, Mogens; Weckwerth, Wolfram; Vestergård, Mette; Retzer, Katarzyna (Frontiers in Plant Physiology, 2023)
The need for increasing for crop productivity leads to a higher usage of synthetic fertilizers, which has tremendous effects on the environment. Nitrogen (N) is a crucial plant macronutrient, but the production of synthetic N fertilizer and its leakage into aquatic systems represent sources of environmental damage. To reduce the usage of synthetic fertilizers, current studies addressed innovative approaches to develop "N-self-fertilizing" crops that can utilize atmospheric nitrogen through enhanced interaction with the root microbiome. In this review we discuss recently obtained knowledge about the role of root hairs and their functions in root exudate secretion for plant-microbiome interactions. Recent studies have shown the beneficial impact of root hairs and exudate secretion on the recruitment of N2 fixing bacteria. Root hair plays a crucial role in shaping the rhizosphere, and first insights into the biological processes that underpin root hair formation and function in relation to microbiome interaction were gained. We summarize to which extent this knowledge can be applied to develop cereals with an enhanced ability to benefit from N2 fixing bacteria. Finally, we describe non-destructive methods and their limitations to study root hair growth directly in the field under natural growth conditions.